Multi Population Evolutionary Programming Approach for Distributed Generation Installation - M.F. Baharom; M.H. Jali; M. Fani; W.M. Bukhari; Z.H. Bohari; M.N M. Nasir; N. Adnan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
This paper describes the impact of the distribution development in order to identify optimum location and sizing for distribution generation (DG) in power system network. Highly demand on the load will lead to in control power distributed by introducing power losses via transmitting the power. Therefore, small-scale electricity generation is required to ensure the large power generated can be used for particular location to minimize losses. In addition, the implementation of distribution generation will slightly reduce the capital cost compared to existing power plant due to space, speed and source required. Thus, proper DG location will significantly enhance the impact on the power flow analysis by considering the source of energy easily obtained. This study will be conducted by using Matlab and the proposed algorithm (MPEP)will be applied on IEEE 30 buses radial distribution system network. As results, the DG is located at optimal locations and sizes rely on the losses consume in various type of DGs technology system used in the network. On the others hand, the condition and location DG itself will generate the optimal power contribution depends on the design strategies that have been implemented.